The Correlation Between Reading Habit And Reading Comprehension Achievement Among the Eleventh Grade Students Of SMA Budi Murni 2 Medan - Clinta Natasa Sitepu; Viator Lumban Raja; Fiber Y.A. Ginting (ANFA MEDIATAMA, 2023)
Reading habit is an reading activity on a regular basis that involves both physically and mentally to get the message, knowledge conveyed by the author. Reading comprehension is the process of making meaning from text.This study was aimed to the see correlation between Students' reading habit and students' reading comprhension at the Eleventh Grade of SMA Budi Murni 2 Medan. The design of the research is a quantitative. The sample of this research is XI 6 and XI 7 class, consist of 65 students. Techniques of data collection used are questionnaire and test. Techniques of data analysis used are SPSS version.16 and Pearson's product moment. Based on data analysis, first, the result of this study indicated that students' reading habit at the Eleventh Grade of SMA Budi Murni 2 Medan is 0.59 Low category. The Second, students’ mean score reading comprehension at the Eleventh Grade of SMA Budi Murni 2 Medan is 82, high category. There is a significant correlation between students' reading habit and students' reading comprehension at the Eleventh Grade of SMA Budi Murni 2 Medan this is accordance with the results of the questionnaire and score test about reading comprehension with significant value rxy=0,707 ≥ =0,367 at a significant level of 5%. This means that the more reading habit the students have the higher their reading comprehension achievement is.